Comparison of HBV-specific T cell reactivity across the pregnant, postpartum and non-pregnant women with chronic HBV infection - Wang, Genju; Yue, Fangping; Zhang, Ziyue; Wu, Yandan; Ji, Ruixue; Zhou, Guanlun; Ji, Ying; Shen, Chuanlai (Frontiers in Immunology, 2024)
Objective: To investigate the features of HBV-specific T cell reactivity across the pregnant, postpartum or non-pregnant women with chronic HBV infection. Methods: A total of 283 patients with chronic HBV infection were enrolled in this study, including 129 patients during pregnancy, 58 patients during postpartum less than 6 months and 96 non-pregnant patients at childbearing age. A universal ELISpot assay was set up using a broad-spectrum T-cell epitope peptide library which containing 103 functionally validated CD8 + T-cell epitopes derived from overall HBsAg, HBc/eAg, HBx and HBpol proteins and fitting to the human leukocyte antigen polymorphisms of Chinese population. Then, The functional HBV-specific T cells in peripheral blood were detected. Results: The spot-forming units (SFUs) of HBV-specific T cells in the pregnant group showed no statistical difference from the postpartum group, but significantly less than that in the non-pregnant group (p = 0.046). In the untreated patients, the pregnant group displayed HBe/cAg-specific T cells (SFUs) less than the non-pregnant group (P = 0.025) and the postpartum group (P = 0.045). Meanwhile, in the NUCs-treated patients, the three groups presented similar HBV-specific T cell reactivity. Furthermore, the SFUs in the NUCs-treated pregnant group were similar to that in the NUCs-untreated pregnant group. Importantly, ROC analysis demonstrated that the HBV-specific T cells (SFUs) (AUC = 0.742) and combined with HBsAg levels (AUC = 0.775) or with HBeAg level (AUC = 0.78) had a good predictive performance for hepatitis progression during pregnancy group.Pregnancy can reduce HBV-specific T cell reactivity in the women with chronic HBV infection, and NUCs treatment cannot improve their HBV-specific T cells reactivity.